Climate variability and international trade - Geoffrey Dunbar; Walter Steingress; Ben Tomlin (Bank of Canada, 2023)
This paper quantifies the impact of hurricanes on seaborne international trade to the United States. Using geocoded hurricane data mapped to satellite tracking data for commercial ships, we identify hurricane intersections on sea-trade routes between U.S. and foreign ports. Matching the timing of hurricane-trade route intersections with monthly U.S. port-level trade data, we isolate the unanticipated effects of a hurricane hitting a trade route using two separate identification schemes: an event study and a local projection. Our estimates imply that a hurricane reduces route-specific monthly U.S. import flows by 5.4% to 16.0%, leading to an aggregate loss of 1.15% to 3.42% of annual U.S. west coast imports for an average storm season. We find no evidence of trade catching up in the months following a hurricane nor any evidence of rerouting to other ports or other transportation modes (e.g., air). Using our estimates in combination with climate scenarios from the Intergovernmental Panel on Climate Change, we quantify a range of costs of future hurricane disruptions that could occur if trade routes remain fixed.
Keywords: C22; C5; F14; F18; Q54; 330; Climate change; International topics